2016
DOI: 10.1007/s11121-015-0630-3
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Outreach and Drop-in Linkage Versus Shelter Linkage for Connecting Homeless Youth to Services

Abstract: Outreach and service linkage are key for engaging marginalized populations, such as homeless youth, in services. Research to date has focused primarily on engaging individuals already receiving some services through emergency shelters, clinics, or other programs. Less is known about those who are not connected to services and, thus, likely the most vulnerable and in need of assistance. The current study sought to engage non-service-connected homeless youth (N = 79) into a strengths-based outreach and advocacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 38 publications
1
39
1
Order By: Relevance
“…Although each of the proposed policy, public, and service interventions are expected to be beneficial to pet owners experiencing homelessness across the lifespan, youth have unique needs related to their developmental stage, reasons for homelessness (e.g., family rejection, childhood abuse and trauma), and approach to help-seeking that necessitate considerations in service delivery models [ 113 ]. Drop-in centers, which provide basic services with minimal barriers, such as food, hygiene, and some healthcare, are youth’s preferred location to access services [ 114 ]. Drop-in centers are uniquely appealing to youth experiencing homelessness because of their low-barrier approach with few restrictions and regulations, and despite the simplicity of this service model, drop-in centers operate as key entry points linking youth to other supports to help them exit homelessness, including housing and job training [ 115 , 116 ].…”
Section: Considerations For Youth Experiencing Homelessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although each of the proposed policy, public, and service interventions are expected to be beneficial to pet owners experiencing homelessness across the lifespan, youth have unique needs related to their developmental stage, reasons for homelessness (e.g., family rejection, childhood abuse and trauma), and approach to help-seeking that necessitate considerations in service delivery models [ 113 ]. Drop-in centers, which provide basic services with minimal barriers, such as food, hygiene, and some healthcare, are youth’s preferred location to access services [ 114 ]. Drop-in centers are uniquely appealing to youth experiencing homelessness because of their low-barrier approach with few restrictions and regulations, and despite the simplicity of this service model, drop-in centers operate as key entry points linking youth to other supports to help them exit homelessness, including housing and job training [ 115 , 116 ].…”
Section: Considerations For Youth Experiencing Homelessnessmentioning
confidence: 99%
“…Drop-in centers are uniquely appealing to youth experiencing homelessness because of their low-barrier approach with few restrictions and regulations, and despite the simplicity of this service model, drop-in centers operate as key entry points linking youth to other supports to help them exit homelessness, including housing and job training [ 115 , 116 ]. Studies have found that youth referred to drop-in centers, rather than emergency shelters, reported more service linkages, less substance use, and better HIV-related outcomes [ 114 , 117 ].…”
Section: Considerations For Youth Experiencing Homelessnessmentioning
confidence: 99%
“…Yet to date, relatively little research has focused on understanding these settings, their effects on youth, and gaps that remain. Some past studies have been conducted on single behavioral interventions for RHY, such as HIV prevention programs ( 17 , 18 ), and a modest number of other studies have described individual programs or a small number of organizations ( 17 , 19 , 20 ). This study takes a qualitative approach to extend this past research by focusing on RHY clients’ perspectives on their experiences in a diverse set of RHY-specific settings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, outreach efforts targeting youth who do not use drop‐in centers have successfully engaged youth in services (Slesnick et al. ). Another limitation is the receipt of services elsewhere (besides a drop‐in center) was only asked of youth who reported needing the service, but denied receiving it at a drop‐in center.…”
Section: Discussionmentioning
confidence: 99%
“…Drop‐in centers are often a homeless youth's initial resource for services (Slesnick et al. , ; Pergamit and Ernst ; Shillington, Bousman, and Clapp ), and these centers provide daytime shelter and basic need services such as food, hygiene, and clothing. Case management and other health, education, employment, and housing services may be offered as well, either on‐site or through referrals (Beechinor and Matsushima ; Shillington, Bousman, and Clapp ), placing drop‐in centers in a unique position to help engage youth in higher‐level services to address behavioral health problems.…”
Section: The Present Studymentioning
confidence: 99%